Pacing for complete heart block in pregnancy - Viljoen, Charle; Hoevelmann, Julian; Sliwa, Karen; Chin, Ashley (SA Heart Journal, 2022)
Whereas sinus tachycardia and paroxysmal supraventricular tachycardia are common during pregnancy, bradyarrhythmias are infrequent. Moreover, bradyarrhythmias are generally well tolerated during pregnancy. Nevertheless, a 12-lead ECG is indicated for pregnant women who present with bradycardia, to rule out sinoatrial (SA) node dysfunction or AV conduction abnormalities. Third-degree AV block (complete heart block, CHB) requires multidisciplinary care during pregnancy, with combined input from Cardiologists and Obstetricians. As CHB is associated with increased mortality and morbidity if left untreated, permanent pacing is usually indicated during pregnancy, even if the patient remains asymptomatic. However, not all pregnant patients with CHB require urgent pacing. In a pregnant patient who has CHB with an escape rhythm with narrow QRS complexes and rate of >50bpm, permanent pacemaker implantation can be delayed until after delivery, as described in this case report.